Buddhism towards Thai Culture in the Northern, Thailand - Suansamran, Suriya Bhuripanyo (BUDDHO, 2022)
Buddhism has a significant influence on the culture, wisdom, and way of life of the people in northern Thailand. The region is known for its beautiful cultural traditions, customs, and the spiritual essence of the Lanna people, which are deeply rooted in nature and the teachings of Buddhism. Buddhism serves as a spiritual center for the people in northern Thailand, and it encompasses every aspect of their lives from birth to death. Practices such as chanting, participating in temple ceremonies on important Buddhist holidays, and offering alms to monks every morning are common. These traditions have been passed down through generations and serve to preserve the cultural heritage associated with Buddhism, bringing benefits and happiness to the Lanna people for a long time.